The Role of Military Training in Improving Psychological Resilience and Reducing Depression Among College Freshmen - Guo, Rui; Sun, Meng; Zhang, Chi; Fan, Zebin; Liu, Zhening; Tao, Haojuan (Frontiers in Psychiatry, 2021)
Background: Military training plays an important protective role in enhancing mental health. However, the effects of military training on psychological resilience and depression among college freshmen in China remain unclear. The present study aimed to evaluate changes in psychological resilience and depression through military training among college freshmen, and to investigate associated psychosocial factors including childhood trauma that may influence its effects on psychological resilience. Methods: A prospective and self-comparison study design was employed. College freshmen who received 3 weeks of military training were recruited. Socio-demographic variables were collected and childhood trauma exposure was estimated by the Childhood Trauma Questionnaire (CTQ). The Connor-Davidson Resilience Scale (CD-RISC) and Patient Health Questionnaire (PHQ-9) were used to assess psychological resilience and depression before and after the military-style training. Results: The military training significantly increased the total and subscale scores of CD-RISC (p < 0.001), and decreased the PHQ-9 score (p < 0.001). The proportion of students with clinical depression reduced from 10.5% at baseline to 7.2% after the training (p < 0.001). Improvement of CD-RISC scores was positively affected by male gender and urban area, while negatively affected by older age, and higher baseline scores of PHQ-9 and CTQ. A significant correlation was found between changes in scores of CD-RISC and PHQ-9 through the training (r = −0.238, p < 0.001). Conclusions: Military training may have a positive effect on increasing psychological resilience and reducing depressive symptoms among college freshmen, especially in male students and those from an urban area, while older age, childhood trauma, higher depression levels, and resilience at baseline may weaken, or even mask its positive effect. Follow-up research should be considered for the long-term effects of military-style training.